Original paperImpedance cardiography in haemodynamic monitoring of septic patients: a prospective study - Piechota, Mariusz; Irzmański, Robert; Banach, Maciej; Kowalski, Jan; Pawlicki, Lucjan (Archives of Medical Science, 2007)
Introduction: The aim of the study was to evaluate the usefulness of impedance cardiography (ICG) in monitoring of septic patients. Material and methods: It was a prospective study performed in 20 consecutive patients with sepsis. The criteria of sepsis according to the definition accepted at the ACCP/SCCM conference were the basis for being enrolled in the study. Six patients died in the course of the study and the investigated group was divided into subgroups treated effectively and ineffectively. Results: The quality of ICG signal was determined in all 128 measurements. The quality of ICG was ³70% in 53.91% of the measurements, ³30% in 88.28% of the measurements. In 11.72% of the measurements the signal quality was <30%. In the effectively treated subgroup the values of NT-proBNP concentration in blood and the number of scores in SOFA were significantly lower (p<0.05), and a moderate positive significant correlation was found between SOFA score and stroke volume, cardiac output and index, acceleration index and NT-proBNP concentration. A significant negative correlation was demonstrated in relation to systemic vascular resistance index, left ventricular ejection time, mean arterial pressure, systolic and diastolic blood pressure. The following indices had a positive correlation with NT-proBNP concentration: heart rate, cardiac output and acceleration index. In the ineffectively treated subgroup only NT-proBNP concentration correlated with SOFA score. Conclusions: ICG is a useful method for monitoring septic patients. It has an advantage over SOFA score. Indices investigated with ICG correlate with NT-proBNP concentration.